2019
DOI: 10.1016/j.adolescence.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness as a mediator for college students' social skills and experiences of depression and anxiety

Abstract: Introduction-Rates of anxiety and depression are increasing among college undergraduates. Existing research has demonstrated a link between social skills and mental health outcomes. This study explores the relationship between verbal social skills (encoding and decoding) and anxiety and depression by measuring the extent to which loneliness mediates these relationships. Methods-Baseline data from a cross-sequential study exploring college student mental health was used to analyze social skills, loneliness, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 72 publications
7
107
0
10
Order By: Relevance
“…Specifically, in relation to academic anxiety, previous research has found that it is strongly predicted by students' self-regulation processes, which tend to be activated at the perception of challenging events [56]. Students with high anxiety levels are inclined to express worse evaluations of their social interactions compared to their low anxiety peers [57,58]. Overall, the results of this study support the status of trait emotional intelligence as a fundamental antecedent variable with a strong impact on students' school adjustment outcomes [24,59].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in relation to academic anxiety, previous research has found that it is strongly predicted by students' self-regulation processes, which tend to be activated at the perception of challenging events [56]. Students with high anxiety levels are inclined to express worse evaluations of their social interactions compared to their low anxiety peers [57,58]. Overall, the results of this study support the status of trait emotional intelligence as a fundamental antecedent variable with a strong impact on students' school adjustment outcomes [24,59].…”
Section: Discussionmentioning
confidence: 99%
“…Ketika seseorang terus menerus memperhatikan hal negatif, maka hal ini memantik stres pada dirinya atau bahkan depresi (Wenzlaff & Bates, 1998). Kesepian berkaitan dengan gangguan mental emosional seperti depresi dan kecemasan pada mahasiswa baru (Brandy, Penckofer, Solari-Twadell & Velsor-Friedrich, 2015;Moeller & Seehuus, 2019). Penelitian di beberapa negara, seperti Inggris, Rusia, dan Swiss telah menyebutkan kesepian sebagai variabel yang berhubungan dan/atau menyebabkan munculnya gangguan mental emosional, seperti depresi, kecemasan, stres dan gangguan somatik (Richardson, Elliot, & Roberts, 2017;Rohrmann dkk., 2017;Stickley dkk., 2016).…”
Section: Pendahuluanunclassified
“…Their use of the internet is generally legitimate in that it helps them connect with friends, retrieve information, play games, and many other attractive, often necessary, activities. O'Donnell and Epstein (2019) wrote that today's students in the United States would almost prefer Internet connectivity than food because of the genuine need for friendships and connections as they transition to adulthood (Kim, Wang, & Oh, 2016;Moeller & Seehus, 2019). As college students, many courses require the use of Internet access for research, coursework completion, and occasionally course participation.…”
Section: The Internet and Hyper-connectivitymentioning
confidence: 99%